4-hydroxyquinolin-2(1H)-one isolated in cryogenic argon and xenon matrices: tautomers and photochemistry - Secrieru, Alina (2024)
4-Hydroxyquinolin-2(1H)-one (4HQ2O) was synthesized, isolated in cryogenic matrices (argon and xenon), and studied by infrared spectroscopy. Quantum chemical calculations carried out at the DFT(B3LYP)/6-311++G (3df,3pd) level of theory were used to determine the conformational and tautomeric properties of the molecule. Two tautomeric forms were identified in the as-deposited matrices with the help of the theoretical data. To investigate the photochemistry of the compound, in situ broadband ultraviolet (lambda > 283 nm) irradiation of the asdeposited argon matrix was performed. This irradiation led to the generation of an additional tautomer, together with the products of fragmentation of the heterocyclic ring of the molecule, specifically isocyanic acid and carbon monoxide. Photoproducts such as 1,3-dihydro-2H-indol-2-one and cyclohepta-1,2,4,6-tetraene were also observed in the photolyzed argon matrix. A comprehensive assignment of the infrared spectra of all the species observed experimentally is presented.